Sustainable Agricultural Policy Strategies to Support the Existence of Subsistence Agriculture in Lingga Regency - wijaya, Mendra; amri, Pahmi (Universitas Muhammadiyah Yogyakarta, 2022)
The production of subsistence farmers dominates Lingga's agricultural commodities as an alternative food supply. However, this production helps meet food needs in Lingga Regency. Along with the development of regional development, to meet the needs and regional food security and guard against land conversion activities, it is necessary to protect agricultural land. This article aims to identify the implementation of the Sustainable Food Agricultural Land Protection Program in Lingga Regency, Riau Islands Province. This research is a qualitative study with a study approach that examines the government's efforts to overcome land conversion and support the productivity of subsistence farmers as alternative food suppliers by making policies to protect agricultural land for sustainable food. Research shows that to anticipate the occurrence of land conversion, the local government of Lingga Regency issued two regulations to ensure the protection of sustainable agricultural land and the determination of the area of rice fields. This study still has limitations, namely respondents for primary data sources, especially in farmer groups. As a result, additional research will be conducted to include subsistence farmers and monitor the policy progress of the sustainable Food and agriculture land conservation program in Lingga Regency.